Radiation and confinement in 0D fusion systems codes. (31st May 2016) - Lux, H; Kemp, R; Fable, E; Wenninger, R
Abstract: In systems modelling for fusion power plants, it is essential to robustly predict the performance of a given machine design (including its respective operating scenario). One measure of machine performance is the energy confinement time τ E that is typically predicted from experimentally derived confinement scaling laws (e.g. IPB98(y, 2)). However, the conventionally used scaling laws have been derived for ITER which—unlike a fusion power plant—will not have significant radiation inside the separatrix. In the absence of a new high core radiation relevant confinement scaling, we propose an ad hoc correction to the loss power P L used in the ITER confinement scaling and the calculation of the stored energy W t h by the radiation losses from the 'core' of the plasma P r a d, c o r e . Using detailedASTRA  / TGLF simulations, we find that an appropriate definition of P r a d, c o r e is given by 60% of all radiative losses inside a normalised minor radius ρ c o r e = 0.75 . We consider this an improvement for current design predictions, but it is far from an ideal solution. We therefore encourage more detailed experimental and theoretical work on this issue.